Investment and Identity: A Phenomenological Study of Accounting Students Financial Self-Discovery - Mongan, Frischa Faradilla Arwinda; Alimuddin; Said, Darwis; Mendra, Ni Putu Yuria (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This interpretive phenomenological study explores how accounting students develop their financial identity through digital investments, explicitly addressing the persistent gap between their theoretical knowledge and practical investment behavior. Utilising in-depth interviews and thematic induction with three students who actively engage in digital investment platforms, the research uncovers that financial identity formation is an existential process, shaped by the intersection of academic rationality, emotional profit/loss experiences, and powerful socio-digital influences. Investment acts as a reflective mirror, aligning students' identity development with responsibility and self-control, consistent with the identity moratorium phase. Importantly, this process reveals significant cognitive dissonance: formal financial knowledge, such as financial statement analysis, is frequently superseded by digital intuition driven by fast-paced information from finfluencers, social media, and real-time news updates. Biases like Fear of Missing Out (FOMO) amplify reliance on rapid digital inputs, leading digital literacy to exert greater influence on investment decisions than formal financial literacy. The study highlights that experiential learning, emotional responses to investment outcomes, and active participation in digital communities contribute to a dynamic, negotiated financial identity among students, integrating logic, emotion, and evolving digital norms. These findings emphasise the necessity for accounting education to enhance behavioural finance and digital literacy modules. Hence, students are better prepared to manage both rational decision-making and the emotional pressures of digital investment. The study contributes new qualitative insights for educators and policymakers by documenting how digital environments transform financial identity and investment behavior among future accountants.